Serum- and albumin-free cryopreservation of endothelial monolayers with a new solution. (3rd April 2018) - Pless-Petig, Gesine; Knoop, Sven; Rauen, Ursula
ABSTRACT: Cryopreservation is the only long-term storage option for the storage of vessels and vascular constructs. However, endothelial barrier function is almost completely lost after cryopreservation in most established cryopreservation solutions. We here aimed to improve endothelial function after cryopreservation using the 2D-model of porcine aortic endothelial cell monolayers. The monolayers were cryopreserved in cell culture medium or cold storage solutions based on the 4°C vascular preservation solution TiProtec ®, all supplemented with 10% DMSO, using different temperature gradients. After short-term storage at −80°C, monolayers were rapidly thawed and re-cultured in cell culture medium. Thawing after cryopreservation in cell culture medium caused both immediate and delayed cell death, resulting in 11 ± 5% living cells after 24 h of re-culture. After cryopreservation in TiProtec and chloride-poor modifications thereof, the proportion of adherent viable cells was markedly increased compared to cryopreservation in cell culture medium (TiProtec: 38 ± 11%, modified TiProtec solutions ≥ 50%). Using these solutions, cells cryopreserved in a sub-confluent state were able to proliferate during re-culture. Mitochondrial fragmentation was observed in all solutions, but was partially reversible after cryopreservation in TiProtec and almost completely reversible in modified solutions within 3 h of re-culture. The superior protection of TiProtec and its modifications was apparent at all temperature gradients; however, best results were achieved with a cooling rate of −1°C/min. In conclusion, the use of TiProtec or modifications thereof as base solution for cryopreservation greatly improved cryopreservation results for endothelial monolayers in terms of survival and of monolayer and mitochondrial integrity.